Reviews of Books (International review of mission, 1954)
Books Reviewed in this article: THE JOURNALS OF MATTHEW RICCI: China in the Sixteenth Century: The Journals of Matthew Ricci, 1583–1610. CHURCH HISTORY IN JAPAN: Kindai Nippon no Keiseid to Kirisuto-kyo: Meiji Shoki Purotestanto Kyokai-shi Ron. HINDU ETHICAL THOUGHT: Social Ethics in Modern Hinduism. By Roland W. Scott. MORAL PHILOSOPHY IN NEO-CONFUCIANISM: La Philosophie Morale dans le Néo-Confucianisme. (Tcheou Touen-yi.) By Chow Yih-ching. ASIA***REVEALED THROUGH RELIGION: Meditation and Piety in the Far East. By K. L. Reichelt. THE MOMENTUM OF CHRISTIAN FELLOWSHIP: A History of the Ecumenical Movement 1517–1948. Edited by Ruth Rouse and Stephen Charles Neill. THE WHOLENESS OF RELIGIOUS EDUCATION: Education into Religion. By A. Victor Murray. ISRAEL ACCLAIMED: Rebirth and Destiny of Israel. By David Ben Gurion. Edited and translated from the Hebrew under the supervison of Mordekhai Nurock, Minister of Israel in Australia. New York: Philosophical Library. USD10.00. 1954. THE SOUTH AFRICAN SCENE: Racial Separation in South Africa. By Eugene P. Dvorin. URBAN NATIVE COURTS IN NORTHERN RHODESIA: The Administration of Justice and the Urban African. THE CONCEPTION OF THE CHIEF IN BANTU SOCIETY: Chiefs and Gods. Religious and Social Elements in the South Eastern Bantu Kingship. (Studia Theologica Lundensia No. 3.) By Olof Pettersson. Lund: Gleerup. Kr. 30. 1953.